Flexural Strength and Fracture Resistance of Leucite-Reinforced Glass Ceramic for Dental CAD/CAM - Hurbag, Meryem; Nalbant, Asude Dilek; Tokar, Emre (The Journal of Dentists, 2018)
Statement of the Problem: Leucite-reinforced CAD/CAM ceramics are aesthetic restorative materials with a very close value of translucency, fluorescence and opalescence to natural teeth, however their flexural strength and fractural resistance values should be evaluated. The purpose of this systematic review was to analyze the fracture resistance and flexural strength values of leucite-reinforced CAD/CAM ceramic materials among the literatures published between 2008 and May 2018. Materials and Methods: An electronic research for articles in English-language, published between 2008 and May 2018 was performed with the help of PubMed search engine. The keywords used were IPS Empress CAD, Rosetta BM, flexural strength, fracture resistance. After applying the predetermined inclusion criteria; the definitive list of selected articles was suitable only for analyzing the flexural strength and fracture resistance values of leucite reinforced CAD/CAM ceramics. Literatures evaluating other ceramics and other criteria such as ‘fatigue resistance’ and ‘optical properties’ were excluded. Results: The systematic application of inclusion criteria resulted in 18 literatures that analyzed the fractural resistance and flexural strength of leucite-reinforced CAD/CAM restorative material. 17 literatures conducted researches about IPS Empress CAD ceramic and 1 was about Rosetta BM ceramic, since it is a new ceramic. Conclusion: For IPS Empress CAD restorative material, the literatures scanned indicated superior aesthetic properties however limited success rate at flexural strength and fractural resistance, especially when compared with IPS E.max CAD restorative material which is more recommended for posterior restorations. For Rosetta BM ceramic; only one literature was found; which reported that Rosetta BM ceramic showed better fracture and strength values when compared to IPS Empress CAD ceramic. However more investigations are needed to be done for both materials in order to develop leucite-reinforced CAD/CAM materials usage; especially in the posterior regions.